Dual-polarization two-port fiber-optic gyroscope - Wang, Zinan (Springer theses,, 2017)
This thesis demonstrates and investigates novel dual-polarization interferometric fiber-optic gyroscope (IFOG) configurations, which utilize optical compensation between two orthogonal polarizations to suppress errors caused by polarization nonreciprocity. Further, it provides a scheme for dual-polarization two-port IFOGs and details their unique benefits. Dual-polarization IFOGs break through the restriction of the "minimal scheme, " which conventional IFOGs are based on. These innovative new IFOGs have unique properties: They require no polarizer and have two ports available for signal detection. As such, they open new avenues for IFOGs to achieve lower costs and higher sensitivity.